From state agencies to ordinary citizens: reframing risk-mitigation investments and their impact to disrupt urban risk traps in Lima, Peru. (October 2017) - Allen, Adriana; Zilbert Soto, Linda; Wesely, Julia; ,; Belkow, Teresa; Ferro, Vladimir; Lambert, Rita; Langdown, Ian; Samanamú, Amaru
The understanding of linkages between disaster risk and urban development has seen important advances in recent decades. However, it falls short in addressing the production and reproduction of so-called urban "risk traps", which are accumulation cycles of everyday risks and small-scale disasters with highly localized impacts, particularly on impoverished urban dwellers. Drawing on the action-research project cLIMA sin Riesgo, this paper examines risk-mitigating investment actions of state agencies, residents and communities in Barrios Altos, in the historic centre of Lima, Peru, and José Carlos Mariátegui, in the periphery. The analysis shows that residents tend to be caught in risk traps not necessarily due to lacking investments, but paradoxically despite them and their unintended effects. Furthermore, accumulated fragmented investments erode the capacity to act of those at risk and perpetuate risk accumulation cycles. The paper argues for a re-assessment of risk-mitigation investments and their intended and unintended consequences, and suggests routes to address current shortcomings in order to disrupt "risk traps".